1985
DOI: 10.1039/p19850002555
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric synthesis of 3-methyl-2-phenyl-1,4-benzodioxanes. Absolute configuration of the neolignans eusiderin and eusiderin C and D

Abstract: The asymmetric synthesis of 2SI3S-and 2R,3S-3-methyl-2-phenyl-l,4-benzodioxane from (-) -ephedrine is reported. Comparison of the c.d. curves of these compounds with those of the natural ncolignans eusiderin and eusiderin C allows the assignment of 2R,3R configuration to eusiderin and of 2R,3S configuration to eusiderin C and eusiderin D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 1 publication
(1 reference statement)
3
70
0
Order By: Relevance
“…The opposite CD signs unambiguously confirm the previously proposed configurational assignments of the erythro-8.4′-oxyneolign-8′-enes 1a-g based on Arnoldi and Merlini's CD result 14 as correct, and hence they can be used as reference. Moreover, the negative specific rotation of (7R, Table 2), have the 7S,8R absolute configuration.…”
Section: 08supporting
confidence: 74%
“…The opposite CD signs unambiguously confirm the previously proposed configurational assignments of the erythro-8.4′-oxyneolign-8′-enes 1a-g based on Arnoldi and Merlini's CD result 14 as correct, and hence they can be used as reference. Moreover, the negative specific rotation of (7R, Table 2), have the 7S,8R absolute configuration.…”
Section: 08supporting
confidence: 74%
“…The coupling constant (J 7,8 ϭ8.4 Hz) between H-7 and H-8, and the NOE correlations between H-8/H-6 and H-7/H-9 clearly indicated a threo configuration of the chiral centers on the dioxane ring. 34,35) The absolute configurations at C-7 and C-8 were determined by the circular dichroism (CD) spectral comparison with the analogous neolignans, eusiderins, whose absolute configurations were determined based on the CD comparison with synthetic analogs 36) as follows. To remove a contribution of a double bond conjugated with the A-ring in 1, a dihydro-derivative 1a which has similar chromophoric system to those of the reference compounds was prepared by catalytic hydrogenation over PtO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…A survey of the literature revealed that an epimer of 3 with the 7S,8S-form was synthesized previously. 24 Pharbilignan D (4) had the molecular formula C 20 (Table 2) of 4 were similar to those of phellinsin A, except for the presence of an ethoxy group, which suggested that compound 4 was the same lignan-type as phellinsin A. 25 The lignan skeleton was verified by HMBC correlations of H-7/C-2, C-6, C-9, C-8′, and C-9′; H-8/C-1, C-7′, and C-9′; and H-7′/C-8, C-2′, C-6′, and C-9′ (Figure 3).…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%